Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Lizy

\(\left\{{}\begin{matrix}\left(x-1\right)\left(y-2\right)=xy-2\\\left(x+1\right)\left(y+2\right)=xy+6\end{matrix}\right.\)

Nguyễn Lê Phước Thịnh
10 tháng 1 2024 lúc 22:19

\(\left\{{}\begin{matrix}\left(x-1\right)\left(y-2\right)=xy-2\\\left(x+1\right)\left(y+2\right)=xy+6\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}xy-2x-y+2=xy-2\\xy+2x+y+2=xy+6\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}-2x-y=-4\\2x+y=4\end{matrix}\right.\Leftrightarrow\left(x,y\right)\in R\)


Các câu hỏi tương tự
tranthuylinh
Xem chi tiết
Lizy
Xem chi tiết
Lizy
Xem chi tiết
Lizy
Xem chi tiết
Ha Pham
Xem chi tiết
Lizy
Xem chi tiết
Thục Quyên
Xem chi tiết
ILoveMath
Xem chi tiết
ILoveMath
Xem chi tiết